The concept of Ordnungspolitik: Rule-based economic policy-making from the perspective of the Freiburg School - Jan Schnellenbach (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2021)
Should economic policy be guided by rules? In this paper, we take the perspective of the Freiburg School and trace its argument for rule-based Ordnungspolitik back to the roots of the concept. In doing so, will not offer a comprehensive review of the literature, but argue closely along the works of Walter Eucken, whose works are central to understanding the founding generation of the Freiburg School. We argue that there are costs of not having rules and therefore that the main thrust of the Freiburg approach is still valid. There are good, empirical arguments for pursuing a rule-based Ordnungspolitik in order to avoid the costs of discretionary policy-making. Furthermore, we argue that a reliance on stable rules does not imply an incapacitation of democratic decision-making. Rules rely on democratic support, and rule-based Ordnungspolitik also leaves substantial material scope for discretionary democratic decision-making.
Keywords: B15; B25; B41; H11; P48; P50; 330; Ordnungspolitik; Freiburg School; economic orders; economic constitutions